Experimental assessment of cracked steel beams under mechanical loading and elevated temperatures - Ahmadi, Bashir, author; Mahmoud, Hussam, advisor; van de Lindt, John, committee member; Strong, Kelly, committee member (Colorado State University. Libraries, 2016)
Bridge fire is a major engineering problem that has been gaining attention by researchers and engineers. As reported in the New York Department of Transportation database, there has been approximately 50 cases of bridge collapse due to fire nationwide with many more cases where fires resulted in repairable damage. The fires are typically due to vehicle crash, arson, and in some cases wildfires. The affected bridges are mostly fabricated from steel, concrete, and temper. The problem of bridge fire is further aggravated by the presence of fatigue cracks in steel bridges. Various experimental and numerical studies have been conducted to evaluate the response of steel beams under elevated temperature. However, to date, there is lack of information on the response of steel beams with pre-existing cracks under elevated temperature. The importance of evaluating cracked steel beams under elevated temperature stems from the fact that many steel bridges that are currently in service suffer from major deteriorations manifested in the presence of fatigue cracks that are the result of cyclic loading from daily traffic. With no available data on failure behavior of cracked steel beams under fire, this thesis introduces a new testing protocol for evaluating the response of cracked steel beams under elevated temperature. Specifically, the results of experimental tests, conducted at the structural engineering laboratory at Colorado State University, of four initially cracked W8x24 steel beams under point loading and non-uniform elevated temperature are presented. The cracks are introduced across the bottom flange and the beams are loaded to failure while being subjected to various non-uniform elevated temperature distributions varying from 200 °C to 600 °C. The competition between two different failure modes: excessive deflection and fracture along the crack plane, is evaluated with respect to temperature distributions in the beams. In cases where fracture prevailed, different types of fractures were observed including brittle fracture, ductile fracture, and brittle/ductile transition failure, which depended on the temperature distribution. The results presented include load versus displacement and time versus temperature curves. In addition, digital image correlation method was utilized to develop strain and displacement fields around the cracked regions. This experimental study provides an alternative method for evaluating cracked beams under elevated temperature and will provide engineers with insight into various behavioral aspects of steel beams under the investigated loading demands. Furthermore, the results of this study can be used to calibrate advanced numerical finite element models, capable of capturing large deformations and fracture, which can in turn be used to conduct a parametric study for various sizes of bridge girders under an ensemble of thermal loading scenarios.
Keywords: cracked steel beam; steel beam under fire; steel at elevated temperature; bridge fire